Factors influencing human papillomavirus vaccine uptake among parents and teachers of schoolgirls in Saudi Arabia: a cross-sectional study - Fallatah, Deema I.; Khalil, Mohammad Adnan; Abd ElHafeez, Samar; Gouda, Salma; Alshanbari, Huda M.; Awadalla, Maaweya; Ahram, Mamoun; Alosaimi, Bandar (Frontiers in Public Health, 2024)
Introduction Cervical cancer is a highly prevalent disease among women worldwide. However, the advent of a vaccine against HPV, the main cause of the disease, has prevented its spread. The acceptability of the HPV vaccine to different sectors of the Saudi community has yet to be clarified. Since parents and teachers are major influencers in the decision-making process of vaccination for HPV, this study aimed to assess the knowledge and attitudes of teachers and parents toward cervical cancer, HPV, and the HPV vaccine, and unraveled the factors that would influence recommending the vaccine. Methods A cross sectional study was done among 927 individuals (373 teachers and 356 parents). A newly developed validated questionnaire was used to collect data on knowledge, attitude, and factors influencing cervical cancer, HPV, HPV vaccine. The relationship between different factors with knowledge and attitude were assessed using univariate and multivariate analysis. Results Of the study participants, 94% were females, with a median (Interquartile range) age of 38(31–44) years, 12.2% were teachers, 38.7% were parents and 49.1% were parents and teachers. The majority (78.5%) were married, and 75.6% had at least one child. Among those with children, 88.6% had at least one girl, and among those with girls, 72.2% had at least one girl aged between 10 and 18 years. The total median (IQR) knowledge score was 9 [(−5)–(−26)] and the total median (IQR) attitude score was 49 (43–56). The knowledge score significantly increased by receiving postgraduate education, working in the health or education sectors, if a person knew someone diagnosed with cervical cancer, having girls in the age group of 10–18 years, reading about medical issues or having previously heard about the HPV vaccine. The attitude score significantly increased by high knowledge score and decreased if the person has previously diagnosed with cervical cancer. Conclusion Physician’s recommendation and the amount of information on the HPV vaccine, opinions about vaccines in general, and government decrees are the main factors influencing decision on HPV vaccine Uptake. This study emphasizes the role of healthcare providers, awareness of cervical cancer, HPV and its vaccine, and social status, in favoring vaccine uptake in Saudi Arabia.